Workplace Violence and Turnover Intention Among Psychiatrists in a National Sample in China: The Mediating Effects of Mental Health - Chen, Yanhua; Wang, Peicheng; Zhao, Lina; He, Yanrong; Chen, Nuoya; Liu, Huanzhong; Liu, Yuanli; Liu, Tingfang; Tang, Yi-lang; Jiang, Feng; Zhu, Jiming (Frontiers in Psychiatry, 2022)
Background Workplace violence (WPV) in healthcare has received much attention worldwide. However, scarce data are available on its impact on turnover intention among psychiatrists, and the possible mechanisms between WPV and turnover intention have not been explored in China. Methods A cross-sectional survey was conducted among psychiatrists in 41 tertiary psychiatric hospitals from 29 provinces and autonomous regions in China. A stress-strain-outcome (SSO) model was adopted to examine the effects of WPV on mental health and turnover intention. The association and mediation by burnout and stress were examined by multivariate logistic regression (MLR) and generalized structure equation modeling (GSEM). Results We invited 6,986 psychiatrists to participate, and 4,520 completed the survey (64.7% response rate). The prevalence of verbal and physical violence against psychiatrist in China was 78.0 and 30.7%, respectively. MLR analysis showed that psychiatrists who experienced verbal violence (OR = 1.15, 95% CI = 1.10–1.21) and physical violence (OR = 1.15, 95% CI = 1.07–1.24) were more likely to report turnover intention. GSEM analysis showed that burnout (β = 4.00, p < 0.001) and stress (β = 1.15, p < 0.001) mediated the association between verbal violence and turnover intention; similarly, burnout (β = 4.92, p < 0.001) and stress (β = 1.80, p < 0.001) also mediated the association between physical violence and turnover intention. Conclusions Experience of WPV is a significant contributor to turnover intention among psychiatrists. Mental health status, such as burnout and stress level significantly mediated the association. Policy makers and hospital administrators need to be aware of this association. Action is needed to promote mental health among the psychiatrists to improve morale and workforce sustainability.